Sleep Quality in Head and Neck Cancer - Giancarlo Pecorari; Simone Moglio; Dario Gamba; Marco Briguglio; Ester Cravero; Eugenio Sportoletti Baduel; Giuseppe Riva (Current Oncology, 2024)
Background: Patients with head and neck cancer often experience impaired sleep. Moreover, the treatment may negatively affect sleep quality. The aim of this observational study was to evaluate the sleep quality after treatment for head and neck cancer, and its relationship with quality of life and psychological distress. Methods: A total of 151 patients who underwent treatment for head and neck cancer at our department were included in the study. Quality of life, sleep quality, risk of sleep apnea, sleepiness, pain, and psychological distress were assessed by means of specific questionnaires. Results: The median follow-up was 30 months. Poor sleep quality was observed in 55.6% of the cases. An association between PSQI global sleep quality and EORTC global health status was found. The DT, HADS anxiety, and HADS depression scores were associated to PSQI global score, sleep quality, sleep latency, sleep disturbances, and daytime dysfunction. Conclusions: Sleep disturbances, particularly OSA and insomnia, are frequent in HNC patients, and significantly impact their quality of life and psychological well-being. Given the effect of sleep on overall well-being, addressing sleep disorders should be a priority in the care of HNC patients.